Mental health issues in pregnant women in Nepal - van Teijlingen, Edwin; Simkhada, Padam; Devkota, Bhimsen; Fanning, Padmadharini; Ireland, Jillian; Simkhada, Bibha; Sherchan, Lokendra; Silwal, Ram Chandra; Pradhan, Samridhi; Maharjan, Shyam K; Maharjan, Ram K (Nepal Journal of Epidemiology, 2015)
Mental health of pregnant women and new mothers is a growing area of concern in both low- and high-income countries. Maternity services in the UK, for example, have focused more attention on maternal mental health. We recognise that pregnancy, birth and the postnatal period is a time of major psychological and social change for women.